Penerapan Rantai Nilai Global Sebagai Strategi Peningkatan Ekspor Produk Kopi - Arief Darmawan; Lili Adi Wibowo; Adhie Surachman (Coopetition : Jurnal Ilmiah Manajemen, 2021)
Coffee farmers as Green MSMEs can apply SDG-based global value chains (GVC) in order to open up a wider share of the export market. During the 2009-2018 period, there was a significant decline in the share of Indonesia's coffee exports, but on the other hand, the impact on the formation of the GDP of plantation crops seemed insignificant. The study attempts to map this problem by analyzing the relationship between the variables that play a role in the formation of GDP (as the dependent variable), namely the volume of coffee production, the export value of coffee, the export price of coffee, and the MSME investment credit during the 2009-2018 period. This research uses a quantitative based approach to obtain multiple linear regression models that can map research problems. Based on statistical tests, the research variables have a positive and significant contribution to the increase in the GDP of plantation crops. The implication of the results is the trend of declining exports substituted by the booming demand for coffee in the country supported by MSME investment credit. The application of GVC can be one strategy to increase the share of coffee exports again.